Nitrogen Utilization in Lemna: I. Relations between Net Nitrate Flux, Nitrate Reduction, and in Vitro Activity and Stability of Nitrate Reductase - Ingemarsson, Björn (1987)
Cultures of Lemna gibba L. G3 were maintained at a constant, N-limited growth rate by adding nitrate daily in amounts calculated to sustain a rate of culture N increment of 0.20 day(−1). Nitrate added to the culture was consumed within 8 to 10 hours and the partitioning to reduction and accumulation during this phase corresponded to, on the average, 75 and 25% of net uptake, respectively. The calculated rate of nitrate reduction was stimulated by onset of net uptake without delay and decreased when net uptake ceased. NADH-nitrate reductase (NR) activity measured in vitro without inclusion of antiproteolytic agents more than doubled during the first hour after nitrate addition and then gradually fell to its original level over the rest of the 24 hour interval. In the presence of the proteinase inhibitor leupeptin during extraction, however, NR activity was in general much higher and without any apparent cycles. The relative stabilizing effect of leupeptin was greatest on NADH-NR and reduced flavin adenine mononucleotide-NR activities whereas the effect was less on NADH-cytochrome c reductase activity (diaphorase) and reduced methylviologen-NR activity. The constant nitrate reductase activity measured in the presence of proteinase inhibitors is assumed to reflect the physiological situation. It thus appeares that short-term changes in nitrate assimilation by N-limited Lemna is related to the flux of nitrate to the reducing site and not to changes in nitrate reductase activity.